Carvedilol to prevent decompensation of cirrhosis in patients with clinically significant portal hypertension stratified by liver stiffness: study protocol for a randomied, double-blind, placebo-controlled, multicentre trial in China - Jie Li; Yan Wang; Fang Wang; Tianyu Liu; Xiao Liang; Yiling Li; Xiaolong Qi; Liting Zhang; Ping Chen; Jian Fan; Ju Huang; Zhujun Cao; et al. (BMJ Open)
Introduction Patients with clinically significant portal hypertension (CSPH) are recommended to be treated with non-selective beta-blockers (ie, carvedilol) to prevent the first hepatic decompensation event by the renewing Baveno VII consensus. CSPH is defined by hepatic venous pressure gradient (HVPG)≥10 mm Hg; however, the HVPG measurement is not widely adopted due to its invasiveness. Liver stiffness (LS)≥25 kPa can be used as a surrogate of HVPG≥10 mm Hg to rule in CSPH with 90% of the positive predicting value in majority aetiologies of patients. A compelling argument is existing for using LS≥25 kPa to diagnose CSPH and then to initiate carvedilol in patients with compensated cirrhosis, and about 5%–6% of patients under this diagnosis criteria may not be benefited from carvedilol and are at risk of lower heart rate and mean arterial pressure. Randomised controlled trial on the use of carvedilol to prevent liver decompensation in CSPH diagnosed by LS remains to elucidate. Therefore, we aimed to investigate if compensated cirrhosis patients with LS≥25 kPa may benefit from carvedilol therapy.Methods and analysis This study is a randomised, double-blind, placebo-controlled, multicentre trial. We will randomly assign 446 adult compensated cirrhosis patients with LS≥25 kPa and without any previous decompensated event and without high-risk gastro-oesophageal varices. Patients are randomly divided into two groups, with 223 subjects in group A and 223 subjects in group B. Group A is a carvedilol intervention group, while group B is a placebo group. All patients in both groups will receive aetiology therapies and are followed up at an interval of 6 months. The 3-year incidences of decompensated events of cirrhosis-related and liver-related death are the primary outcome. The secondary outcomes include development of each complication of portal hypertension individually (ascites, variceal bleeding or overt hepatic encephalopathy), development of spontaneous bacterial peritonitis and other bacterial infections, development of new varices, growth of small varices to large varices, delta changes in LS and spleen stiffness, change in hepatic dysfunction assessed by Child-Pugh and model for end-stage liver disease score, change in platelet count, development of hepatocellular carcinoma, development of portal vein thrombosis and adverse events with a 3-year follow-up. A predefined interim analysis will be performed to ensure that the calculation is reasonable.Ethics and dissemination The study protocol has been approved by the ethics committees of the Sixth People’s Hospital of Shenyang (2023-05-003-01) and independent ethics committee for clinical research of Zhongda Hospital, affiliated to Southeast University (2023ZDSYLL433-P01). The results from this trial will be submitted for publication in peer-reviewed journals and will be presented at international conferences.Trial registration number ChiCTR2300073864.